DENSITY OF Clostridium perfringens BACTERIA AND HETEROTROFIC BACTERIA IN RIAU DUMAI SEA WATER AND RESISTENCE TEST ON ITS ANTIBIOTICS - Situmorang, Adrian; F. Feliatra, F. Feliatra; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This  research was conducted in April to June 2018 in the Dumai Sea Waters of Dumai City, Riau , Privince. The purpose of this study was to determine the level density of C. perfringens and heterotrophic bacteria, analyze the level of resistance of C. perfringens and heterotrophic bacteria to antibiotics. The method used in research is an experimental method. Biochemical and resistance test analyzes were performed at the marine Microbiology Laboratory of the Faculty of study, the calculation of the number of C. perfringens and heterotrophic bacteria from the five stations obtained from the waters shows that the number C. perfringens bacteria is lower if compared with the number of heterotrophic bacteria that are in the five stations. The highest density of C. perfringens bacteria at station 3 with  a value of 1,5 x 106 and the lowest station 4 with a value 2,1 x 105. The average results of testing of te antibiotic Chloramphenicol found that all bacterial isolates were sensitive, and in isoniazid antibiotic testing it was found that all bacterial isolates were resistant. Keywords : Density, Resistance test and C. perfringens and heterotrophic bacteria